UNUSUAL INITIAL PRESENTATION OF PRIMARY ANTIPHOSPHOLIPID SYNDROME AS POSTPARTUM SYMMETRICAL PERIPHERAL GANGRENE - Khan, Marium Marufia; Shahid, Sana; Zafar, Amara; Khan, Nudrat Naz; Bhatty, Shaheen (Journal of Ayub Medical College Abbottabad, 2022)
Antiphospholipid syndrome (APS) is an acquired prothrombic state with recurring thromboembolic and obstetric complications in the presence of antiphospholipid antibodies. Isolated skin manifestation especially symmetrical peripheral gangrene (SPG) in postpartum phase is reported rarely. To highlight this unusual presentation of APS with SPG we present a case of young female who developed SPG on her third postpartum day. Postpartum period runs a high risk of sepsis but development of such extensive and rapid ischemic changes in APS is seen uncommonly.